2017
DOI: 10.1136/bjsports-2017-098253
|View full text |Cite
|
Sign up to set email alerts
|

European normative values for physical fitness in children and adolescents aged 9–17 years: results from 2 779 165 Eurofit performances representing 30 countries

Abstract: This study provides the largest and most geographically representative sex-specific and age-specific European normative values for children and adolescents, which have utility for health and fitness screening, profiling, monitoring and surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
350
11
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(474 citation statements)
references
References 59 publications
(23 reference statements)
38
350
11
20
Order By: Relevance
“…In the anthropometric, physical and motoric values obtained in the study, it was observed that there were differences depending on the gender variable, which is consistent with the literature data [6,25,26]. It was observed that the female students in Kosovo were taller and heavier than their male peers until the age of 13, which is the case in their peers in other countries as well.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the anthropometric, physical and motoric values obtained in the study, it was observed that there were differences depending on the gender variable, which is consistent with the literature data [6,25,26]. It was observed that the female students in Kosovo were taller and heavier than their male peers until the age of 13, which is the case in their peers in other countries as well.…”
Section: Discussionsupporting
confidence: 80%
“…The balance scores obtained in the study were compared with the norm values reported by Tomkinson et al after 123655 measurements in 19 countries. It was observed that the normal values of the male and female students in Kosovo were worse balance ability scores according to the values in the 50 percentile reported in the study conducted by Tomkinson except for 13 and 14 years of age [6]. Again, the balance scores were compared with the balance scores obtained by Jürimäe & Volbekiene (1998) in Estonia in students from similar age groups.…”
Section: Pedagogics Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Successful examples are the Assessing Levels of Physical Activity study (ALPHA study) [8], which aimed to identify reliable fitness tests for children and adolescents; the AVENA study, which aimed to evaluate cardiovascular fitness in youth around Europe [9]; the Healthy Lifestyle in Europe by Nutrition in Adolescence study (the HELENA study) [10], which evaluated physical fitness over 10 European nations; FitnessGram [11], whose purpose was to increase the levels of physical activity in children in the United States; and EUROFIT [12], a program in Europe. All these attempts firstly detected the reliability of the fitness tests for specific populations and secondly provided age-related fitness percentile values [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These tests were the standing broad jump for the evaluation of lower limb strength, the hand-grip test for the evaluation of the strength of the upper limbs, the sit-up to exhaustion for the evaluation of abdominal muscular endurance, the 4 × 10-m shuttle run for the evaluation of agility, and the 20-m shuttle run test for the evaluation of aerobic capacity. Notwithstanding that such a fitness battery was used in adolescents, other studies such as AVENA, FitnessGram, or EUROFIT, have used similar fitness batteries to evaluate physical fitness levels in children [11,12,16,17]. Another similar battery is that proposed by the PREFIT study used in Spanish schoolchildren [18].…”
Section: Introductionmentioning
confidence: 99%